The last happy marriage: a peculiar representation of women in soap operas - Yaranga Hernández, Mayra Rosario (2013)
In the last few years, despite major breakthroughs in the access to information and education,the representation of women in the media seems to have remained in a stereotyped image ofold. A particular example of this appears in telenovelas, which constitute a crucial element in theformation of women’s identity, but tend to suggest images ranging in an easily identifiable “good/evil” binomial, without regard for a person’s complex nuances. However, there are examplesshowing an attempt to move beyond such frames. One of them is the Colombian telenovelaEl último matrimonio feliz (The last happy marriage), starting from a social fact (the increasingnumber of failing marriages) to portray, in a more realistic way, women who have to overcomesuch a situation.